Music and youth culture in Latin America identity construction processes from New York to Buenos Aires - Vila, Pablo 1952- (Currents in Latin American and Iberian music, 2014)
This book tries to demystify commonsense assumptions about youth culture in Latin America. The musical manifestations that young people listen to in most Latin American countries are not only much more varied than the commercially successful ones that have entered the American and European markets, but also do not have much in common with the American and European commonsense image of the young people who listen to and dance to them. Music and Youth Culture in Latin America is an initial attempt to overcome this deficit. In this collection of essays, we examine the ways in which music is used to advance identity claims in several Latin American countries and among Latinos in the United States. From young Latin American musicians who want to participate in the vibrant jazz scene of New York without losing their cultural roots, to Peruvian rockers who sing in their native language (Quechua) for the same reasons, passing through the experience of young Cubans who use music to construct a post-communist social identification, the book sheds a new light on the complex ways in which music occupies center stage in many processes of identification in Latin America.